2012
DOI: 10.1111/mpp.12010
|View full text |Cite
|
Sign up to set email alerts
|

Hexanoic acid is a resistance inducer that protects tomato plants against Pseudomonas syringae by priming the jasmonic acid and salicylic acid pathways

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 55 publications
(87 reference statements)
4
98
0
Order By: Relevance
“…cinerea (Angulo et al, 2015). syringae (Vicedo et al, 2009;Scalschi et al, 2013). In addition, recent reports showed the role of OPDA in the pathogen-induced callose accumulation (Scalschi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…cinerea (Angulo et al, 2015). syringae (Vicedo et al, 2009;Scalschi et al, 2013). In addition, recent reports showed the role of OPDA in the pathogen-induced callose accumulation (Scalschi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Hx treatment has been reported to protect tomato plants against hemi-biotrophic bacterium P.syringae pv tomato DC3000 (Vicedo et al, 2009). Recently, some studies have revealed that in this pathosystem, Hx treatment seems to counteract the negative effect of pathogen coronatine (COR), which requires JA-Ile on the SA pathway (Scalschi et al, 2013 (Britto and Kronzucker, 2002). This may include leaf chlorosis, lower plant yield production and root/shoot ratio, lower cation content, acidification of the rhizosphere, and changes in several metabolite levels, such as amino acids or organic acids (Britto and Kronzucker, 2002;Bittsánszky et al, 2015).…”
Section: Priming Stage Induced By Natural or Quemical Compoundsmentioning
confidence: 99%
See 3 more Smart Citations